Nanodiamond-containing composites for tissue scaffolds and surgical implants: A review - Zamani, Yasamin; Zareein, Ali; Bazli, Leila; NasrAzadani, Reyhaneh; Pasha Mahammod, Babar; Nasibi, Shima; Modarresi Chahardehi, Amir (Journal of Composites and Compounds, 2020)
Due to promising properties such as low toxicity against different cell lines, being highly stable fuorescent without showing photobleaching, and good surface properties, nanodiamonds have gained ever-increasing attention for various biomedical applications including bioimaging and therapeutic applications. Various methods are used for the fabrication of nanostructured diamond, the commonly used of which is the denotation technique. Newer approaches are being practiced for the modifcation and functionalization of their surfaces by different biomolecules suitable for interaction with considered targets. In this review, the scope and recent advancement in the feld of nanodiamonds for biomedical applications particularly their application for nanocomposite scaffold and implants are discussed.